Experimental evaluation of remaining prestress force and center negative bending-moment in railroad ties removed from track after 25 years of service - Scott, James Daniel (Kansas State University, 2019)
To better understand the appropriate level of prestress force necessary in a prestressed concrete railroad tie that will both mitigate the propensity for longitudinal splitting and also result in a long-term service life, a study was conducted on 12 different designs of existing ties removed from track to evaluate the remaining prestress force in the ties. The existing ties selected for the study had performed well in track for over 25 years and remained in good condition upon removal from track, with no signs of longitudinal splitting. Four different experimental test methods were conducted to evaluate the remaining prestress force in the existing ties. The experimental methods used included the flexural crack reopening method, the newly developed direct tension method, the strain gage method, and the measurement of the length change of wires extracted from the ties. New ties were manufactured with internal vibrating-wire strain gages to provide ties with known prestress forces at the time of testing, and used for comparison to the experimental results. Test results indicate that the direct tension test was the most accurate of the four methods, and that existing ties tended to have prestressing forces in the range of 82-93 kips. Additional testing was conducted to evaluate the center negative cracking moments of the existing ties and compare the results to the current requirements of the AREMA Chapter 30 center negative bending-moment test. Results indicate that of the 12 tie designs investigated, 8 would meet the requirements of the AREMA 30 test in their current state. Knowing current condition and track performance of the existing ties, their level of remaining prestress force, and their center negative bending capacity, new ties could be designed with similar parameters to ensure a durable long-term performance in track while reducing the longitudinal splitting propensity of the tie.
Keywords: Railroad ties; Prestress force; Splitting propensity